Coelomycetes of Assam-I - U.N. SAIKIA, M.S. ALI and (Indian Phytopathology, 2002)
Studies on Phyllosticta species in Assam with special reference to the sheathed and appendiculate nature of their conidia revealed the existence of 10 species of the genus of which the teleomorphic state of P. dieffenbachiae, Guignardia dieffenbachiae, and P. pterisina are new to science, whereas P. arecae, P. caryotae, P. eucalypti, P. flacourtiae, P. murrayicola, P. musarum, P. subeffusa and P. rosae are hitherto unrecorded from North-East India.